TEACHER IN CITIZENSHIP EDUCATION LEARNING PROCESS - Čekse, Ireta; Geske, Andrejs; Pole, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The recent reforms in the Latvian general education curriculum along with a school network reorganization have brought new attention to the issues related to a teacher education and the level of professionalism in everyday teaching work. Soviet-era education and work experience in diverse political and education systems (under the Soviet rule and after the restoration of independence) are factors that should be taken into account when analyzing the teacher in the citizenship education learning process. For the needs of this Paper, the authors used the data of the IEA ICCS 2016 (International Association for the Evaluation of Educational Achievement International Civic and Citizenship Study 2016) teachers who teach citizenship education-related school subjects (n=249) and their students (N=3224, Grade 8, average age from 13 to 14). To process the data, the authors usedclusters, correlations, regression analysis and descriptive statistics.The aim of this Paper is to study what the teacher is like in the process of citizenship education. The findings allow making two conclusions: First, the teacher’s personality, experience and networking skills plays an important role; Second, the popular assumption among both professionals and nonprofessionals that cooperation between an eighth-grade teachers and parents leads to a better student achievements is false.